Public support for lockdown policies - Boto-Garcia, David (Economics and Business Letters, 2021)
Due to the outbreak of the COVID-19 disease, many countries have been forced to impose non-pharmaceutical policy interventions such as lockdowns to stop community transmission. We investigate public support for the lockdown policy in Spain, one of the countries most affected by the pandemic and with the strictest lockdown in Europe. Based on survey data collected during the first weeks of March and April 2020, we investigate how public support for the lockdown relates to the number of confirmed cases in the province of residence, personal institutional trust and concern about the severity of coronavirus. We find that public approval of the lockdown significantly relates to the evolution of COVID cases, institutional trust, political ideology and personal economic situation.